Relationship Between Self-esteem and Negative Perception Trends About the Body in Early Adults at STIKES Maharani Malang - SetiyoBudi, Anggraeni; Hanurawan, Fattah (KnE Social Sciences, 2022)
This study aims to examine the relationship between self-esteem and the tendency of negative perceptions about the body in early adulthood at STIKES Maharani Malang. This study uses a quantitative approach with a descriptive correlational method. The study amounted 98 female students at STIKES Maharani Malang by using the Purposive Sampling Technique as a sample determinant. The data analysis technique used is the Pearson Product Moment correlation test. Data collection uses an adaptation of the State self-esteem (SSES) by Heatherton and Polivy [1] and a modified Body Dysmorphic Disorder Symptom Scale (BDD-SS) by Wilhelm et al. [2]. The results of hypothesis testing using Spearman Rank correlation with a value of Sig .00 (P < .05), because in the assumption test the data is not normally distributed. The results of the analysis show that there is a positive relationship between self-esteem and the tendency of negative perceptions about the body. Keywords: self-esteem, negative perception tendencies, early adulthood